2018
DOI: 10.1007/s00018-018-2933-6
|View full text |Cite
|
Sign up to set email alerts
|

The master regulator FUBP1: its emerging role in normal cell function and malignant development

Abstract: The human Far Upstream Element (FUSE) Binding Protein 1 (FUBP1) is a multifunctional DNA and RNA binding protein involved in diverse cellular processes. FUBP1 is a master regulator of transcription, translation, and RNA splicing. FUBP1 has been identified as a potent pro-proliferative and anti-apoptotic factor by modulation of complex networks. FUBP1 is also described either as an oncoprotein or a tumor suppressor. Especially, FUBP1 overexpression is observed in a growing number of cancer and leads to a deregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 166 publications
(288 reference statements)
1
50
0
Order By: Relevance
“…Previous reports showed that inactivating mutations of FUBP1 were detected in 15–20% of oligodendrogliomas [ 16 , 50 ], suggesting a tumor suppressive role of Fubp1. However, excessive expression of FUBP1 was documented in a variety of malignancies and FUBP1 abundance was often inversely correlated with overall survival [ 51 ], suggesting an oncogenic role of Fubp1. In the present study, we demonstrated the tumor-promoting function of Fubp1 by showing that Fubp1 transcriptionally activates cyclin A to promote cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that inactivating mutations of FUBP1 were detected in 15–20% of oligodendrogliomas [ 16 , 50 ], suggesting a tumor suppressive role of Fubp1. However, excessive expression of FUBP1 was documented in a variety of malignancies and FUBP1 abundance was often inversely correlated with overall survival [ 51 ], suggesting an oncogenic role of Fubp1. In the present study, we demonstrated the tumor-promoting function of Fubp1 by showing that Fubp1 transcriptionally activates cyclin A to promote cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%
“…108 Both cell-free and cell-based selective 2 0 hydroxyl acylation analyzed by primer extension (SHAPE) analysis showed that the addition of SMN-C2 altered the reactivity of some bases in TSL1, suggesting this compound induces conformational changes of this inhibitory loop. Further, proteomics analysis using a photo-cross-linking probe revealed enrichment of far upstream element binding protein 1 (FUBP1) 109 and far upstream element binding protein 2 (KHSRP). 110 Fluorescence polarization assays with SMN-C2 and recombinant FUBP1 induced higher polarization in the presence of ESE2.…”
Section: Small Molecules Modulate Smn2 Splicingmentioning
confidence: 99%
“…Comparison of TF expression levels and influence scores reveals that 39 of the 186 TFs associated with the nine motif families are strongly correlated with | r |>0.5 and a significant p-value ( Fig 3b ). For example, r <0 for FUBP1 with influence scores close to zero for the nephron progenitors but positive elsewhere, suggests that FUBP1 acts as a repressor in progenitors 32 . ETS family 2 shows a high positive correlation with ELF1 , and our analysis indicates that it is most important in immune cells, consistent with previous studies 33 .…”
Section: Scover Identifies Regulatory Motifs In Human Kidneymentioning
confidence: 99%